Aseptic Meningitis in Infant with Kawasaki Disease - Rattanawilaisak, Kanokorn (Journal of Health Science of Thailand, 2018)
A 3-month old boy presented with high fever, diarrhea and convulsion. Physical examination and laboratory investigation results showed aseptic meningitis. A few days later this patient had erythematous rash and conjunctivitis. His oral cavity and lips were deeply red and unilateral cervical lymph node enlarged and swollen with erythema of palms and soles. Echocardiography showed abnormal diameter and internal lumen changed of coronary artery. Perivascular brightness was seen, mild pericardial effusion. Then the boy was diagnosed asKawasakidisease with meningitis and treated with IVIG and ASA. The clinical symptoms and signs were improved and discharged later. Echocardiography 6th week after discharge from hospital showed normal coronary artery.